PENGARUH SUPPLY CHAIN INTEGRATION DAN SUPPLY CHAIN INFORMATION SHARING TERHADAP KINERJA SUPPLY CHAIN PADA RUMAH MAKAN - Arev Astiti Pinandari (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study aims to analyze the impact of supply chain integration, and supply chain information sharing on supply chain performance at the house dining/restaurant. The main thrust of this study is the first, motivated by the supply chain performance and effective management of the supply chain is increasingly being recognized as an important factor in achieving competitive advantage. Second are motivated by empirical studies of different supply chain performance. The diversity of views on supply chain performance to encourage the emergence of a variety of different empirical studies in terms of constructs, this indicates the need for more specific analysis of predictable factors that can be used to explain why a better supply chain performance. A good supply chain performance within an enterprise is influenced by supply chain integration, and supply chain information sharing. This study uses a quantitative approach through a survey of 78 respondents house dining/restaurant in Yogyakarta. The analytical tool used is the Multiple Regression. The study found that supply chain information sharing is not a factor driving the increased supply chain performance in the context of the house dining/restaurant. There are other factors that become drivers for the increased supply chain performance at the house dining/restaurant, which is supply chain integration.